Numerical Investigation of Rotational Head Impacts in Atrophic Alzheimer’s Brains Using Finite Element Analysis (Development Engineering Conferences Center Articles Database, 2025)
Traumatic brain injury (TBI) is a critical concern in elderly populations, particularly in individuals with Alzheimer’s disease (AD), where brain atrophy may influence injury outcomes. This study employed finite element analysis to investigate the effects of rotational head impacts on two brain models: one representing healthy aging with a 0.5% annual atrophy and another representing AD with a 4% annual atrophy. The peak normal stress in the frontal region was slightly lower in the AD model (0.24803 MPa) compared to the healthy aging model (0.25025 MPa), likely due to increased cerebrospinal fluid thickness. However, the first principal strain at the end of the simulation was higher in the AD model (0.1222) than in the healthy aging model (0.1171), indicating greater tissue deformation. These findings highlight that while atrophy-related CSF increases can reduce stress, they may also enhance relative motion between brain and skull, potentially increasing the risk of injury. Future studies should incorporate patient-specific atrophy patterns and various impact scenarios to better understand brain vulnerability in neurodegenerative conditions.